Desain Dan Penjadwalan Produksi Pit Tambang Batubara CV. Niska, Dusun Senamat, Kecamatan Pelepat, Kabupaten Bungo, Provinsi Jambi - Yudha Kurnia Isti (Departemen Teknik Pertambangan FT UNP, 2023)
Given the still high demand for coal, Indonesian coal mining operations must also be prepared to face conditions of increasing demand for mining products, which require the application of accurate and efficient calculations and proper mine planning, while continuing to create good mining practices in accordance with the Regulation of the Minister of Energy and Mineral Resources No. 26 of 2018, in the sixth part of article 27 which holders of exploration IUP, exploration IUPK, production operation IUP, and production operation IUPK are required to carry out the use of technology, engineering capabilities, design, development, and application of mining technology. CV. Niska has carried out and completed the exploration phase in the Mining Business Permit Area (WIUP) in Senamat Village, Pelepat District, Bungo Regency, Jambi Province. Based on the exploration findings, coal distribution has been found, where exploration drilling and test pits have been carried out in the IUP CV. Niska, who will then open a new Mining Activity in the IUP area, with an area of 199 Ha. After carrying out the Exploration Phase, a mining plan or design must be carried out with specified requirements, specifications, detailed and clear technical standards, as well as a technical sequence of activities to achieve the goals and objectives of the activities. So, to increase the effectiveness and efficiency of the production process and achieve the goal of mining output, production scheduling is very important. After conducting the analysis and discussion, the results obtained from the pit design carried out in the Mining software show that the mining area to be mined is 69.52 Ha. The results of the theoretical study and theoretical calculations, the production scheduling plan (overburden and coal targets) in April 2023 – March 2024 namely, for overburden of 6,472,322 bcm, and for coal of 809,040 tons, and can recommend tools for overburden stripping, namely for every one unit of Komatsu PC 800 excavator can be paired with 4 units of Hino FM 260 JD, for one unit the Komatsu PC 400 excavator can be paired with 4 units of Hino FM 260 JD, and for coal extraction the selected tool is the Komatsu PC 400 excavator which can be paired with 3 units of Hino FM 260 JD. the largest fleet in March 2024 was 7 fleets consisting of 28 units of Hino FM260JD Dump Trucks and 7 units of Komatsu PC400 Excavators. For the Komatsu PC800 Excavator fleet for one year, namely 5 units, and 20 units of Hino FM260JD Dump Trucks